Respostas

2013-11-05T18:43:25-02:00
A) 8x + 12 = 4x + 16   
8x - 4x = 16 - 12
4x = 4
x = 4/4
x = 1
   
b)5x + 10x + 15 - 25x = 20x - 45
5x + 10x - 25x - 20x = - 45 -15
-30x = - 60
x = - 60 / 30
x = -2

c)
6.(2x - 1) - 2.(2x - 6) = 38
12x - 6 - 4x + 12 = 38
12x - 4x = 38 + 6 - 12
8x = 32
x = 32 / 8
x= 4

d)
25x - 35 = 5.(6 - 2x)
25x - 35 = 30 - 10x
25x + 10x = 30 + 35
35x = 65
x = 65 / 35
x = 1,8

e)
2x/4 + 2x/10 = 6
2x + 2x = 6 . 4 . 10
4x = 240
x = 240 / 4
x = 60

f)
x-2/3 + x + 2 = 8
x + x = 8 + 2 . 3 - 2
2x = 28
x = 28 / 2
x = 14